Medication management through pharmacist‐provided home‐based services. Issue 4 (29th April 2020) - Pherson, Emily; Swarthout, Meghan; Fu, Denise; Barbour, Lauren; Green, Robert; Ross, Patricia; Nesbit, Todd
Abstract: Introduction: Pharmacists play an important role in helping patients manage their medications across the continuum of care. Pharmacist home visits support continuity of care and provide a unique opportunity to identify medication‐related problems. Objective: The primary objective of this study was to describe a cohort of patients who received home visits and the subsequent actions taken by the pharmacist towards the goal of optimizing medication regimens. The evolution of the service is also described. Methods: A retrospective chart review was used to gather demographic information. Clinical documentation was reviewed to gather information on medication problems identified by the pharmacist and recommendations made to prescribers. Institutional and city databases were used to collect data on readmissions and socioeconomic status, respectively. Descriptive statistics were used to analyze data. Results: Between February 2012 and December 2018, 485 home visits were conducted. Patients were taking a mean of 13 (SD ±5.5) medications; 1890 medication discrepancies were identified and 862 recommendations were made to prescribers. The relative risk reduction in readmissions for those patients who received a home visit was 6.6%. The average yearly income for citizens who live in neighborhoods where many of the home visits took place was $37 000. Details regarding the evolution of the home visit service were described. Conclusions: A large cohort of 485 home visits demonstrated that medications are often not being taken as prescribed, and that the pharmacist is in a unique position to educate patients and work with providers toward the goal of optimizing medication regimens and behaviors. This model of care, focused on high‐risk patients, has been sustained over 7 years. Ongoing efforts are underway to improve communication with prescribers, increase the referral to home visit conversion rate, and enhance longitudinal outcome tracking. Opportunity exists to further expand the service through partnerships with regional payers.